ORF3a Protein of Severe Acute Respiratory Syndrome Coronavirus 2 Inhibits Interferon-Activated Janus Kinase/Signal Transducer and Activator of Transcription Signaling via Elevating Suppressor of Cytokine Signaling 1 - Wang, Rong; Yang, Xiaofeng; Chang, Mingke; Xue, Ziyang; Wang, Weirong; Bai, Liang; Zhao, Sihai; Liu, Enqi (Frontiers in Microbiology, 2021)
Coronavirus disease 2019 (COVID-19) has caused a crisis to global public health since its outbreak at the end of 2019. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the pathogen of COVID-19, appears to efficiently evade the host immune responses, including interferon (IFN) signaling. Several SARS-CoV-2 viral proteins are believed to involve in the inhibition of IFN signaling. In this study, we discovered that ORF3a, an accessory protein of SARS-CoV-2, inhibited IFN-activated Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling via upregulating suppressor of cytokine signaling 1 (SOCS1), a negative regulator of cytokine signaling. ORF3a induced SOCS1 elevation in a dose- and time-dependent manner. RNAi-mediated silencing of SOCS1 efficiently abolished ORF3a-induced blockage of JAK/STAT signaling. Interestingly, we found that ORF3a also promoted the ubiquitin-proteasomal degradation of JAK2, an important kinase in IFN signaling. Silencing of SOCS1 by siRNA distinctly blocked ORF3a-induced JAK2 ubiquitination and degradation. These results demonstrate that ORF3a dampens IFN signaling via upregulating SOCS1, which suppressed STAT1 phosphorylation and accelerated JAK2 ubiquitin-proteasomal degradation. Furthermore, analysis of ORF3a deletion constructs showed that the middle domain of ORF3a (amino acids 70 to 130) was responsible for SOCS1 upregulation. These findings contribute to our understanding of the mechanism of SARS-CoV-2 antagonizing host antiviral response.